2009
DOI: 10.1177/0960327109105160
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study on respiratory effect of toner exposure

Abstract: In this baseline study, part of a cohort study to clarify the effect of toner exposure on the respiratory system, we surveyed 803 male toner workers and 802 referents with regard to their subjective respiratory symptoms and chest X-ray results. We also examined individual exposure history, current working conditions, and personal exposure levels to toner. There was a significantly higher prevalence of “coughing and sputum” related complaints among toner-exposed workers in the 30 and 40-year age groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Office laser printers are major emission sources of nanoparticles including carbon nanoparticles (He et al, 2007;Morawska et al, 2009). Cross sectional studies indicated a greater prevalence of radiographic abnormalities and decreased lung function in workers dealing with printing toner dust (Nakadate et al, 2006;Terunuma et al, 2009). And a recent case study demonstrated that carbon +nanoparticles aggregated under the mesothelium in the peritoneum along with inflammatory responses, and nanoparticles got distributed via lymphatic and blood circulation post inhalation into the lung (Dirk et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Office laser printers are major emission sources of nanoparticles including carbon nanoparticles (He et al, 2007;Morawska et al, 2009). Cross sectional studies indicated a greater prevalence of radiographic abnormalities and decreased lung function in workers dealing with printing toner dust (Nakadate et al, 2006;Terunuma et al, 2009). And a recent case study demonstrated that carbon +nanoparticles aggregated under the mesothelium in the peritoneum along with inflammatory responses, and nanoparticles got distributed via lymphatic and blood circulation post inhalation into the lung (Dirk et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…All the participants are composed of healthy workers with no obvious abnormalities detected by annual health examinations which included routine medical examination, and laboratory tests [complete blood count (CBC), cytochemistry, electrocardiogram (ECG), and chest X-ray]. Details of the study and characteristics of the participants have been described in the previous reports [17,18] .…”
Section: Participant and Data Collectionmentioning
confidence: 99%
“…Grouping regarding toner exposure were derived from the company record of job assignment; (a) toner manufacturing line workers, (b) service engineers, and (c) desk workers (control group). As for the exposure levels to the toners, however, it was not possible to stratify the exposure levels according to the job assignments because the actual exposure levels were very low in both of the subgroup (a) and (b) [17] . Although it would be possible that the sensitivity of measured biomarker levels are too low to assess the biological effect of the toners, apparently the health effects of the toners are minimal if present at all judging from the data comparing smokers and non-smokers where we could see the obvious differences of the biomarkers between smokers and non-smokers [17,18] .…”
Section: Yearmentioning
confidence: 99%
“…When respiratory health of workers in toner manufacturing units were assessed, studies suggested deterioration of respiratory health related to toner dust exposure was less likely to occur in current well controlled work environments [21-23]. …”
Section: Introductionmentioning
confidence: 99%